gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Secondary forest fragments offer important carbon and biodiversity cobenefits - Fabio A. R. Matos; Luiz F. S. Magnago; Carlos Aquila Chan Miranda; Luis F. T. de Menezes; Markus Gastauer; Nathália V. H. Safar; Carlos E. G. R. Schaefer; Mônica P. da Silva; Marcelo Simonelli; Felicity A. Edwards; Sebastião V. Martins; João A. A. Meira‐Neto; et al. (Global Change Biology, 2020)
Tropical forests store large amounts of carbon and high biodiversity, but are being degraded at alarming rates. The emerging global Forest and Landscape Restoration (FLR) agenda seeks to limit global climate change by removing carbon dioxide from the atmosphere through the growth of trees. In doing so, it may also protect biodiversity as a free cobenefit, which is vital given the massive shortfall in funding for biodiversity conservation. We investigated whether natural forest regeneration on abandoned pastureland offers such cobenefits, focusing for the first time on the recovery of taxonomic diversity (TD), phylogenetic diversity (PD) and functional diversity (FD) of trees, including the recovery of threatened and endemic species richness, within isolated secondary forest (SF) fragments. We focused on the globally threatened Brazilian Atlantic Forest, where commitments have been made to restore 1 million hectares under FLR. Three decades after land abandonment, regenerating forests had recovered ~20% (72 Mg/ha) of the above‐ground carbon stocks of a primary forest (PF), with cattle pasture containing just 3% of stocks relative to PFs. Over this period, SF recovered ~76% of TD, 84% of PD and 96% of FD found within PFs. In addition, SFs had on average recovered 65% of threatened and ~30% of endemic species richness of primary Atlantic forest. Finally, we find positive relationships between carbon stock and tree diversity recovery. Our results emphasize that SF fragments offer cobenefits under FLR and other carbon‐based payments for ecosystem service schemes (e.g. carbon enhancements under REDD+). They also indicate that even isolated patches of SF could help to mitigate climate change and the biodiversity extinction crisis by recovering species of high conservation concern and improving landscape connectivity.

Would protecting tropical forest fragments provide carbon and biodiversity cobenefits under REDD +? - Luiz Fernando S. Magnago; Ainhoa Magrach; William F. Laurance; Sebastião V. Martins; João Augusto A. Meira‐Neto; Marcelo Simonelli; David P. Edwards (Global Change Biology, 2015)
Tropical forests store vast amounts of carbon and are the most biodiverse terrestrial habitats, yet they are being converted and degraded at alarming rates. Given global shortfalls in the budgets required to prevent carbon and biodiversity loss, we need to seek solutions that simultaneously address both issues. Of particular interest are carbon‐based payments under the Reducing Emissions from Deforestation and Forest Degradation ( REDD +) mechanism to also conserve biodiversity at no additional cost. One potential is for REDD + to protect forest fragments, especially within biomes where contiguous forest cover has diminished dramatically, but we require empirical tests of the strength of any carbon and biodiversity cobenefits in such fragmented systems. Using the globally threatened Atlantic Forest landscape, we measured above‐ground carbon stocks within forest fragments spanning 13 to 23 442 ha in area and with different degrees of isolation. We related these stocks to tree community structure and to the richness and abundance of endemic and IUCN Red‐listed species. We found that increasing fragment size has a positive relationship with above‐ground carbon stock and with abundance of IUCN Red‐listed species and tree community structure. We also found negative relationships between distance from large forest block and tree community structure, endemic species richness and abundance, and IUCN Red‐listed species abundance. These resulted in positive congruence between carbon stocks and Red‐listed species, and the abundance and richness of endemic species, demonstrating vital cobenefits. As such, protecting forest fragments in hotspots of biodiversity, particularly larger fragments and those closest to sources, offers important carbon and biodiversity cobenefits. More generally, our results suggest that macroscale models of cobenefits under REDD + have likely overlooked key benefits at small scales, indicating the necessity to apply models that include finer‐grained assessments in fragmented landscapes rather than using averaged coarse‐grained cells.

Iron speciation in minerals and glasses probed by $$\hbox{M}_{2/3}$$ M 2 / 3 -edge X-ray Raman scattering spectroscopy - A. Nyrow; C. Sternemann; M. Wilke; R. A. Gordon; K. Mende; H. Yavaş; L. Simonelli; N. Hiraoka; Ch. J. Sahle; S. Huotari; G. B. Andreozzi; A. B. Woodland; et al. (Contributions to Mineralogy and Petrology, 2014)

Site response studies and seismic microzoning in the Middle Aterno valley (L’aquila, Central Italy) - G. Lanzo; F. Silvestri; A. Costanzo; A. d’Onofrio; L. Martelli; A. Pagliaroli; S. Sica; A. Simonelli (Bulletin of Earthquake Engineering, 2011)

Radiolabelling of engineered nanoparticles for in vitro and in vivo tracing applications using cyclotron accelerators - N. Gibson; U. Holzwarth; K. Abbas; F. Simonelli; J. Kozempel; I. Cydzik; G. Cotogno; A. Bulgheroni; D. Gilliland; J. Ponti; F. Franchini; P. Marmorato; et al. (Archives of Toxicology, 2011)

Recorded ground motion and site effects evaluation for the April 6, 2009 L’Aquila earthquake - M. Maugeri; A. L. Simonelli; A. Ferraro; S. Grasso; A. Penna (Bulletin of Earthquake Engineering, 2011)